Urban eco-greenergy (TM) hybrid wind-solar photovoltaic energy system and its applications - Chong, W.T.; Muzammil, W.K.; Fazlizan, A.; Hassan, M.R.; Taheri, H.; Gwani, M.; Kothari, H.; Poh, S.C. (2015)
This paper introduces the Eco-Greenergy (TM) hybrid wind-solar photovoltaic energy generation system and its applications. The system is an integration of the novel omni-direction-guide-vane (ODGV) with a vertical axis wind turbine (VAWT). The ODGV is designed to surround the VAWT for wind power augmentation by creating a venturi effect to increase the on-coming wind speed before it interacts with the turbine blades. In wind tunnel tests, the ODGV improves the power output of the VAWT by 3.48 times compared with a bare VAWT at its peak torque. Furthermore, the rotor rotational speed of the wind turbine increased by 182 at 6 m/s of wind speed. A solar PV panel can be mounted on the top surface of the ODGV for solar energy generation. Estimation on wind-solar energy output shows that the system can generate a total of 572.8 kWh of energy per year By comparison, the ODGV increases the annual wind energy output by 438. The green energy generated from the hybrid system can be used to power LED lights or other appliances (e.g., CCTV camera).